2012
DOI: 10.1177/001440291207800402
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainability of Schoolwide Positive Behavior Interventions and Supports

Abstract: A summary of the available literature on sustainability is provided and recommended sustainability features are applied to implementation of schoolwide positive behavior interventions and supports (SWPBIS). One hundred and seventeen schools from 6 states completed the sustainability survey, which determined the presence of 8 sustainability features as they related to sustaining schoolwide positive behavior supports. Results from a logistic regression analysis demonstrate that together the sustainability featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
98
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 44 publications
11
98
1
4
Order By: Relevance
“…Furthermore, the results confirmed that the identified components of sustainability (e.g., McIntosh et al 2011McIntosh et al , 2010McIntosh et al , 2013Coffey and Horner 2012;Sugai and Horner 2006) were important to the concept and were a valid way to examine the sustainability of PB4LSW. The contribution of each factor was considered important such that a full discussion of each is warranted.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Furthermore, the results confirmed that the identified components of sustainability (e.g., McIntosh et al 2011McIntosh et al , 2010McIntosh et al , 2013Coffey and Horner 2012;Sugai and Horner 2006) were important to the concept and were a valid way to examine the sustainability of PB4LSW. The contribution of each factor was considered important such that a full discussion of each is warranted.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, sustainability research must consider the effectiveness of a practice based on empirical evidence linking the practice with desired outcomes, and the careful use of procedures for accurate implementation based on a realistic analysis of their practicality and applicability. From such research, conclusions can be made regarding the sustainability of the practice (Coffey and Horner 2012;McIntosh et al 2011;Vaughn et al 2000).…”
Section: Importance Of Sustainability Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In schools, this means (a) establishing engaged leadership teams, (b) delivering training and support to teams of individuals, (c) providing the resources and time to allow teams to receive training, apply skills/practices learned in training, and (d) adapting procedures in response to data, local cultural, and organizational variables. Schools implementing these practices are more likely to implement PBIS with high fidelity and sustain PBIS with valued student outcomes (Coffey & Horner 2012;McIntosh et al 2010). 3.…”
Section: Implement Bsystems^that Support and Sustain Effectivementioning
confidence: 99%